HIV/AIDS-RELATED KNOWLEDGE, ATTITUDES AND SOCIAL DISTANCE TOWARDS PEOPLE LIVING WITH HIV/AIDS (PLWHA) AMONG UNDERGRADUATE STUDENTS IN CALABAR: Life Science-Psychology - OLAIDE BAMIDELE, EDET; EDET ETIM, EDET; EDOHO, PATIENCE; WILFRED (International Journal of Life Science and Pharma Research, 2012)
The study determines HIV-AIDS related knowledge, attitudes and level of social distance of undergraduate students in Calabar towards PLWHA as a basis for planning an appropriate stigma-reducing educational intervention. A total population study of 165 undergraduate students was undertaken for this descriptive survey. Responses to a validated self-reporting questionnaire provided the source of data. The mean age of participants was 21 +/- 3.6. Eighty seven (53.0%) scored below the mean knowledge score of 11.0 +/- 3.9. One hundred and five (64.0%) had a favourable outlook towards PLWHA. although some myths still exist among the students. Most 109 (66.0%) were classified as desiring moderate to severe distance towards PLWHA. Previous encounter with PLWHA and experience of VCT were significantly associated with knowledge and attitudes of undergraduates (P<0.05). Sensitization seminars on HIV/AIDS targeted at undergraduates should include opportunities for interactive sessions with PLWHA and exposure to VCT.